PHONETIC STUDIES IN AREK SUROBOYO CULTURE LANGUAGES - Nurmalita Herdiana; Yohana Kezia; Citra Dewi Kirana; Endang Sholihatin (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
The phonetic study of the language of the arek surabaya culture is an in-depth study of phonetic characteristics in the language of the surabaya community, known as "the language of the arek surabaya culture." The study aimed at 1) learning phonetic studies in the language of the arek surabaya culture, and 2) knowing the vocabulary and cultural aspects of arek surabaya. This research method USES qualitative methods with data collecting through audio recordings of everyday conversations and interviews with a z generation from arek surabaya. Phonetic analysis includes search of consonants, vowels, intonation, and special accents that characterize the cultural language of arek surabaya. The conclusion of the study: 1 phonetic study of the arek surabaya cultural language where people can see how this phonetic study is derived from the vowels, consonants and intonation of the suroboyoan dialect. 2) the vocabulary and cultural aspects of arek surabaya were able to learn the pronunciation or pronunciation of the dialect of suroboyoan while communicating directly with the other person, as well as by listening to native surabaya speaking in her own language by speaking in the native suroboyoan language that became an outstanding and well-known aspect of the surabaya culture.